Reviewing The Indicators for Assessing Construction Company and Project Performance (Universitas Indonesia, 2022)
This paper is devoted to analyzing and systematizing indicators for assessing the performance of construction companies and projects. This topic is relevant because financial performance and other indicators of sustainable development are increasingly considered when determining the performance of construction companies. The systems of indicators developed by researchers for construction companies and projects are usually based on one of the three performance assessment models: the Balanced Scorecard Model (BSC), the European Foundation for Quality Management (EFQM), and the Key Performance Indicators (KPIs). In this study, we systematized the indicators presented in 18 papers on performance evaluation of construction companies and construction projects, published in 14 journals from 2014 to 2021. The analysis revealed that the top 13 performance factors mentioned in five papers included: safety and health, environment, cost, quality, profitability, time, client satisfaction, innovation, technology & learning, productivity, stakeholder satisfaction, people, business performance, and client & market focus. Thus, the analysis conducted of the scientific literature revealed that researchers’ formation of performance indicators for construction organizations and projects emphasizes the satisfaction of all parties involved in a project’s construction and operation processes. Furthermore, criteria related to safety, overall quality, cost, and environmental impact are found in 50% of the papers, signifying the high importance of these indicators. However, in three articles analyzed, 78% of all identified indicators were mentioned, indicating a lack of consensus within the scientific literature on specific metrics for assessing the performance of construction organizations and construction projects.